Loan-to-Value Policy and Property Loans Risk in Conventional Commercial Banks of Indonesia - Sasikirono, Nugroho; Sudana, I Made; Sumanto, Syelma; Meidiaswati, Harlina (International Research Journal of Business Studies, 2019)
This study aims to determine the effect of loan-to-value (LTV) policy on bank’s property loan risk of Indonesia. This study utilizes a purposive sampling method and multiple linear regression analysis techniques. The number of samples in this study is 66 banks with 563 observations data. The results show that bank’s property loan risk, which is proxied by the NPL ratio of property loans, is lower in the LTV tightening policy period than the easing period. We utilize some control variables in this study: inflation, gross domestic product growth, property loan growth, and bank size. Inflation, property loan growth, and bank size have a significant positive effect on non-performing loans, while gross domestic product growth has a significant negative effect.